Using eye-controlled highlighting techniques to support both serial and parallel processing in visual search. - Pan, Yunxian; Ge, Xianliang; Ge, Liezhong; Xu, Jie (Applied Ergonomics, 2021)
Recent research has developed two eye-controlled highlighting techniques, namely, block highlight display (BHD) and single highlight display (SHD), that enhance information presentation based on a user's current gaze position. The present research aimed to investigate how these techniques facilitate mental processing of users' visual search in high information-density visual environments. In Experiment 1, 60 participants performed 3-, 6-, 9-, and 12-icon visual search tasks. The search times significantly increased as the number of icons increased with the SHD but not with the BHD. In Experiment 2, 40 participants performed a 49-icon visual search task. The search time was faster, and the fixation spatial density was lower with the BHD than with the SHD. These results suggested that the BHD supported parallel processing in the highlighted area and serial processing in the broader display area; thus, the BHD improved search performance compared to the SHD, which primarily supported serial processing.